History, memory, and territorial cults in the highlands of Laos - Petit, Pierre, 1966- author.
1 online resource.
Keywords: "This book captures the dynamics of history, memory, and territorial cults in Houay Yong, a Tai Vat village situated in the multiethnic highland frontier between Laos and Vietnam. Taking seriously the experiences of the villagers, it partakes in a broader movement to reintegrate highlanders and their agency into history at large. Based on comprehensive fieldwork research and the examination of colonial archives, this book makes accessible for an English-speaking audience untapped French archives on Laos and early publications on territorial cults written by French ethnologists. In so doing, it provides a balanced perspective, drawing from the fields of memory studies and classical historical research. Following a chronological approach stretching from the 19th century to the present, it extends narrative analysis through a comparative ethnography of territorial cults, a key component of the performative and material presentification of the past. Highly interdisciplinary in nature, History, Memory and Territorial Cults in the Highlands of Laos will be useful to students and scholars of anthropology, history and religious studies, as well as Asian culture and society"--